Management of Undisplaced and Minimally Displaced Colles’ Fracture with Thermoplastic Splint Versus Conventional Colles Casting - Nadeem Kashmiri, Imtiaz Ahmed Shakir, Rahman Rasool Akhtar, Rana Muhammad Adnan (Journal of Rawalpindi Medical College, 2018)
Background: To compare the outcome in Colles’ fracture treated with thermoplastic splint versus conventional Colles cast. Methods: In this observational study 62 patients having Colles fracture were included. Patients were placed in two groups; group A were treated with Colles’ cast while group B with Thermoplastic splint. Radiographic evaluation was done, using Antero-posterior and lateral view wrist radiographs. Functional outcome assessed with Gartland and Werley Score demerit system. Results: Out of 62 patients, 28 (45.1%) were male with mean age of 38.67 and 34(54.8%) were female patients having mean age of 47.20. The total number of patients that had excellent functional outcome was 34 out of 62 (54.8). The excellent functional outcome was achieved in 16(50%) patients treated with colles brace. However, in patients treated with thermoplastic splint the functional outcome was excellent in 18(60%) patients. Conclusion: Best functional outcome after the treatment of Colles’ fracture is achieved by the use of thermoplastic splint.